PKM Pendampinggan Perluasan Jaringan Wi-Fi Pada Madrasah Ibitidaiyah Al-Azhari - Syaiful Syaiful; Ahmad Ali Afandi; Asik Kurniawan; Arik Wagiyanto; Anugrah Teguh Wahyudi (Universitas Nurul Jadid, 2022)
In this era of digitalization, the internet is an important need to be fulfilled, including in educational institutions. There are several ways that can be used to connect electronic devices to the internet, one of which is a wireless network. Wireless networks are quite attractive because they are more practical and have a fairly wide range. One of the widely used wireless network technologies is Wi-Fi (Wireless Fidelity). The internet network at Madrasah Ibitidaiyah Al-Azhar Karangren has used Wi-Fi technology to connect electronic devices to the internet. However, the Wi-Fi coverage area is liMadrasah Ibitidaiyahted due to the geographical problems of the building that block the Wi-Fi signal, so there are several buildings at Madrasah Ibitidaiyah Al-Azhar Karangren that are not covered by the Wi-Fi network. Therefore, it is necessary to develop a Wi-Fi network by expanding the Wi-Fi coverage area and managing user management, so that all areas and parts of Madrasah Ibitidaiyah Al-Azhar Karangren can use the internet according to their individual needs.